A search for OB stars in the field of the galactic OB association Bochum 7: II. Proper motion and IR photometry - Corti, Mariela Alejandra (2018)
Aims. We plan to identify the members of the Bochum 7 association by performing simultaneous astrometric and spectrophotometric analyses, and estimate its distance and evolutionary stage. Methods. We used our own visual spectroscopic and UBV photometric data of a 300 × 300 region centered at a = 8h44m47:2s, δ =-45°58055.500. This information enabled us to estimate the spectral classification and distance of all stars present in the region. The proper motion was analyzed with data of the UCAC 5 catalog and was used to identify the members of this association. We added JHK data from 2MASS and IRAS catalogs to check for the presence of infrared (IR) excess stars. Results. We found that Bochum 7 is an OB association with at least 27 identified stellar members (l = 265.12, b =-2) at a distance of '5640 pc. Its proper motion is μacosd =-4:92 ± 0:08 mas yr-1, μd = 3:26 ± 0:08 mas yr-1. We derived an average heliocentric radial velocity of ∼35 km s-1 and were able to confirm the binary nature of the (ALS 1135) system and detect four new binary star candidates. Analysis of data for massive Bo 7 star candidates points towards a young age (=3 × 106 years old) for the association, although the presence of a previous episode of star formation remains to be analyzed.